Neuropeptide effects on movements pace in archery - Tambovtseva, R. W.; Sechin, D. I. (Theory and Practice of Physical Culture, 2018)
The experimental study was designed to rate the effects of Semax neuropeptide on the archers` movement pace, with a computerized tapping tests applied for the pace rating purposes. The Semax 0.1% administration in the doze of 500mkg was found to cause changes in the hand movement pace in the six ten-second test intervals. The Semax 0.1% administration was tested to be in the positive correlation with the maximal hand movement pace, reduction of relative body fat mass and relative water content. The study data and analyses show the need for a higher priority to be given to the studies of the effects of different neuropeptides on the physical working capacity.